2018
DOI: 10.1097/qad.0000000000001650
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ischemic stroke risk among women living with HIV infection

Abstract: The increased risk of ischemic stroke among WLWH compared with HIV-uninfected women persisted after adjusting for both traditional and sex-specific stroke risk factors. Further investigation into the mechanisms of elevated stroke risk among WLWH, including immunologic factors, will be key for developing targeted preventive strategies for this at-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…Similarly, these findings may also be found in other developing countries. After adjusting for vascular risk factors, an increased risk of stroke in HIV patients has been found in both men29 and women 30. Possible mechanisms of stroke in HIV-patients are changes in coagulation state, cardioembolism, HIV-associated vasculitis, HIV-associated vasculopathies and mycotic aneurysms 31…”
Section: Epidemiology and Stroke Aetiology From A Global Perspectivementioning
confidence: 99%
“…Similarly, these findings may also be found in other developing countries. After adjusting for vascular risk factors, an increased risk of stroke in HIV patients has been found in both men29 and women 30. Possible mechanisms of stroke in HIV-patients are changes in coagulation state, cardioembolism, HIV-associated vasculitis, HIV-associated vasculopathies and mycotic aneurysms 31…”
Section: Epidemiology and Stroke Aetiology From A Global Perspectivementioning
confidence: 99%
“…In their cohort, 78% of subjects were on PI. Chow et al found a two-fold increase in ischemic stroke in HIV-reactive women compared with healthy controls [18]. Similarly, HIV + individuals on PI had higher Fg values than those in the control group, probably due to drug action [16,56,62].…”
Section: Discussionmentioning
confidence: 97%
“…Chronic infection of HIV promotes changes in hemostasis and coagulation inconsequence of persistent systemic immune activation, micro-and macro-vascular disease, and, potentially, impaired hepatic synthesis of coagulation factors [17]. Futhermore, in these patients, the aging process starts early compared to the general population, due to the increase of complicating factors and other diseases [18][19][20]. Markers of biological and cellular aging are common in HIV-reactive patients [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the Partners cohort, the association between HIV and elevated ischemic stroke risk in women was still present after accounting for traditional vascular risk factors and sex-specific risk factors, including menopause status, estrogen use, history of pregnancy, hypercoagulable disorders, migraines, and a history of depression or anxiety. 38 However, the study's reliance on administrative billing codes to define these risk factors, including menopause, which is inadequately captured by billing codes, challenges the validity of these findings. In the ALLRT cohort, the higher risk of stroke in women compared with men was primarily observed in the 40-to 49-year age group, posing the question of whether hormonal changes (i.e., estrogen depletion) during the perimenopause transition could be a particularly high-risk time for cerebrovascular health in women living with HIV.…”
Section: Potential Mechanisms For Sex Differences In Cerebrovascular mentioning
confidence: 99%